SPP1+ macrophages promote head and neck squamous cell carcinoma progression by secreting TNF-α and IL-1β - Chun Liu; Kun Wu; Chuwen Li; Zhen Zhang; Peisong Zhai; Haiyan Guo; Jianjun Zhang (Journal of Experimental & Clinical Cancer Research)
Abstract Background Head and neck squamous cell carcinoma (HNSCC) is a very aggressive disease characterized by a heterogeneous tumor immune microenvironment (TIME). Tumor-associated macrophages (TAMs) constitute the major innate immune population in the TIME where they facilitate crucial regulatory processes that participate in malignant tumor progression. SPP1 + macrophages (SPP1 + Macs) are found in many cancers, but their effects on HNSCC remain unknown. This study aimed to identify and validate the role and function of SPP1 + Macs in the malignant progression of HNSCC. Methods In this study, we applied single-cell RNA sequencing (scRNA-seq) analyses of paired tumor and normal tissues from 5 HNSCC patients to identify tumor-specific SPP1 + Macs. RT-qPCR and multiplex immunohistochemical and multiplex immunofluorescence staining were used to verify the presence of SPP1 + Macs in the clinical samples. Gene set variation analysis suggested that SPP1 + Macs were actively involved in cytokine production. Thus, we constructed SPP1-OE macrophages and SPP1-KD macrophages (both differentiated from THP-1 cells), performed a Luminex liquid suspension chip detection assay to detect differential cytokines, and further assessed their biological functions and mechanisms in several HNSCC cell lines and adjacent macrophages. An in vivo experiment was used to verify the function of SPP1 + Macs in HNSCC progression. Results The scRNA-seq results revealed that myeloid cells were heterogeneous and strongly correlated with tumor cells in the TIME in HNSCC and identified tumor-specific SPP1 + Macs, which were positively correlated with poor prognosis of HNSCC patients. Gene set variation analysis (GSVA) suggested that SPP1 + Macs were actively involved in cytokine production. Luminex liquid suspension chip detection assay indicated that SPP1 + Mac-derived TNF-α and IL-1β played important roles. Both in vitro and in vivo experiments and the use of VGX-1027, an inhibitor of macrophage-derived TNF-α and IL-1β, confirmed that SPP1 + Mac-derived TNF-α and IL-1β promoted HNSCC progression by supporting tumor cell proliferation and migration. Mechanistically, we found that TNF-α and IL-1β were upregulated due to NF-kappa B signaling pathway activation in SPP1 + Macs. Moreover, SPP1 + Mac-derived TNF-α and IL-1β promoted the expression of OPN in both tumor cells and other adjacent macrophages through different signaling pathways. Conclusions SPP1 + Macs increase the secretion of TNF-α and IL-1β via the NF-kappa B pathway to promote HNSCC cell proliferation, and TNF-α and IL-1β in turn upregulate the expression of OPN in tumor cells and macrophages; thus, SPP1 + Macs may be a candidate target through which antitumor efficacy can be enhanced.